Green Supply Chain Management em pequenas e médias empresas do setor químico - Franco, Denise (Universidade Federal de São Carlos, 2014)
This research aimed to understand how the Green Supply Chain Management (GSCM) is being adopted in small and medium-sized chemical companies. In addition, sought to identify the GSCM practices being adopted by companies in the study and indicate the main pressures (external and internal) for the adoption of these practices. It examine also if the pressures lead to adoption of GSCM practices and if these practices bring improvements in performance (environmental, economic and operational). In order to refine the theoreticalconceptual model of Santa Eulalia, et al. (2011) had conducted a multiple case study in four chemical companies. The companies are small and medium enterprises (SMEs) in the State of São Paulo. The GSCM practices adopted by most companies researched were, respectively, the most adopted for the less practiced, Internal Environmental Management Cooperation with Customers, Green Purchasing, Eco-design and Investment Recovery. The pressures most cited by respondents were, respectively, Regulations, Internal Factor, Marketing, Suppliers and Competitors, and the Society was not considered by any company. It was also found that companies that receive greater pressure to adopt GSCM practices are not always the ones with more practices implemented. However, external and internal factors influencing pressure somewhat implementing GSCM practices. On the performance achieved with the adoption of practices, there is an awareness that bring improved environmental and economic performance. At the same time, the practice can lead to a negative economic impact, especially in the short term. It was also that the positive economic and environmental performance are interrelated. The improvement in operating performance is not perceived by the respondents of the researched companies. Few studies have been found on this issue in national literature, which this study is considered pioneer in research on the theme that analyze the relationships between pressures, practices and performances. Another contribution of the study involves the size of the studied companies, small and medium enterprises (SMEs), since they have few resources, making it difficult to stay in the competitive global market. Studies involving SMEs and to consider its context are relevant to help them gain competitive advantage.
Keywords: Cadeia de suprimentos; Gestão ambiental; Pressão organizacional; Prática administrativa; Desempenho; Environmental supply chain management; Pressures; Practices; Performance; ENGENHARIAS::ENGENHARIA DE PRODUCAO